THE EFFECTIVENESS OF MOBILE PHONE APPLICATION TO IMPROVE GRAMMAR SKILL FOR UNDERGRADUATE STUDENTS - Irham Miftakhul Jannah; Mira Patlasari2; Fahrur Rijal Ardiyanto (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2021)
The aim of this study is to measure the effectiveness of using mobile application in teaching and learning grammar to university students. The application used in this research is Busuu. 28 undergraduate students participated in the study. Busuu mobile application was chosen as a tool for teaching and learning process. It has several function for teachers and students. The benefits of using busuu are, 1. The material used is arranged by users’ grade, 2. It is an interactive media, 3. Students will be evaluated by each development, 4. Easy to be accessed, 5. There is interaction with other users. The next step to monitor the students is extensive review. This qualitative research was designed as experimental research which included pre-test and post-test to measure the result of the effectiveness of using Busuu. The result of the study indicated that the mean score of participants was increased. It means that the use of mobile phone application is effective for teaching and learning process in online learning